New Images for Old Symbols: Meanings That Children Give to a Traditional Game - García-Monge, Alfonso; Rodríguez-Navarro, Henar; Bores-García, Daniel (Frontiers in Psychology, 2021)
Traditional games are considered agents of enculturation. This article explores the procedure to access the cultural meanings transmitted in a traditional game. The goal is to understand what children aged 6-11 make of the game called ‘the chained bear’ and to compare the meanings retrieved with those of different traditional versions of the game. For such a purpose, cartoons depicting people playing the game where exhibited and viewers were asked to interpret them as a drama play, as well as contributing a title, a plot and saying how they would name the characters. The results show that, beyond the individual images that each child created in their mind, most of them coincided in stories about harassment & defense and theft & protection. These plots match those of the ludic tradition, showing that the actions evoke different pictures to each individual, but share common cultural meanings in turn. The experiment shows a procedure to access the meanings that traditional games transmit and confirms that games contain pieces of culture, which makes them agents of enculturation.